2013
DOI: 10.2147/ijn.s43203
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro sustained release profile and antitumor effect of etoposide-layered double hydroxide nanohybrids

Abstract: Magnesium-aluminum layered double hydroxides intercalated with antitumor drug etoposide (VP16) were prepared for the first time using a two-step procedure. The X-ray powder diffraction data suggested the intercalation of VP16 into layers with the increased basal spacing from 0.84-1.18 nm was successful. Then, it was characterized by X-ray powder diffraction, Fourier transform infrared spectroscopy, thermogravimetry and differential thermal analysis, and transmission electron microscopy. The prepared nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…[123][124][125][126][127] Qin et al prepared a nanohybrid formulation of VP16 by intercalating it into Mg/Al LDHs (VP16-Mg/Al LDHs). 128 They found that the nanohybrid (VP16-Mg/Al LDHs) possessed better antitumor activity against MKN45 and SGC-7901 cells. The release of VP16 from LDHs was found to be sustained and followed a diffusion mechanism, as it followed the parabolic kinetic model.…”
Section: Protocatechuic Acid Layered Double Hydroxidesmentioning
confidence: 99%
“…[123][124][125][126][127] Qin et al prepared a nanohybrid formulation of VP16 by intercalating it into Mg/Al LDHs (VP16-Mg/Al LDHs). 128 They found that the nanohybrid (VP16-Mg/Al LDHs) possessed better antitumor activity against MKN45 and SGC-7901 cells. The release of VP16 from LDHs was found to be sustained and followed a diffusion mechanism, as it followed the parabolic kinetic model.…”
Section: Protocatechuic Acid Layered Double Hydroxidesmentioning
confidence: 99%
“…Etoposide (ETP), a semisynthetic derivative of podophyllotoxin, is the inhibitor of deoxyribonucleic acid (DNA) topoisomerase 2 (Qin et al, 2013). Its main effect appears to be at the G 2 portion of the cell cycle in mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, owing to low solubility, drug resistance, and poor bioavailability, the therapeutic efficacy of VP16 is limited. [6][7][8] Therefore, an efficient drug delivery system is desired to overcome these drawbacks and improve the clinical therapy effects.…”
Section: Introductionmentioning
confidence: 99%